2021
DOI: 10.1039/d1cp00100k
|View full text |Cite
|
Sign up to set email alerts
|

Distortion energy-electronic energy compensation determines the nature of solute interactions with irradiation induced vacancies in ferritic steel

Abstract: Fundamental knowledge of point defect (mainly vacancy)-solute (in particular Cu and Ni) interaction at the electronic level is of utmost importance to understand experimentally observed Cu-precipitation in reactor pressure vessel...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…It is shown that the SIA and impurity atom induced strain in the bcc-Fe lattice is reduced due to the formation of complexes. The electron contribution to the binding energy is a result of the redistribution of the electron cloud with the formation of new chemical bonds [26,32]. The distortion binding energy eliminates the destabilizing effect due to the electron binding energy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is shown that the SIA and impurity atom induced strain in the bcc-Fe lattice is reduced due to the formation of complexes. The electron contribution to the binding energy is a result of the redistribution of the electron cloud with the formation of new chemical bonds [26,32]. The distortion binding energy eliminates the destabilizing effect due to the electron binding energy.…”
Section: Discussionmentioning
confidence: 99%
“…) between the Fe atoms in the matrix and the single impurity atoms decreases with increasing n. The strain field around the bcc-Fe substrate is caused by the interaction between the impurity atoms and their first nearest neighbor Fe atoms [25,26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations